Efffcts of nitrogen fertilization rates on forage yield and quality of annual rygrass (Lolium Multiflorum L.) in central black sea climatic zone in TURKEY - Çinar, Selehattin; Özkurt, Mahir; Çetin, R. (Corvinus Univ Budapest, 2020)
In this research, we aimed to determine the effects of nitrogen fertilization on forage yield and forage quality of annual ryegrass (Lolium multiflorum L.) in Kazova, Tokat/Turkey conditions (the Central Black Sea Climate Zone) in 2014/2015 and 2015/2016 growing years. The experiment consisted of four replications in randomized complete block design to test effect of seven nitrogen rates (0, 50, 100, 150, 200, 250, 300 kg ha(-1)) on plant height (PH), fresh forage yield (FFY), dry matter yield (DMY), crude protein ratio (CP), crude protein yield (CPY), Acid Detergent Fiber (ADF) ratio, Neutral Detergent Fiber (NDF) ratio, digestible dry matter ratio (DDM), digestible dry matter yield (DDMY), and relative feed value (RFV). The results revealed that the highest plant height (86.7 cm) was at the 200 kg ha(-1) of nitrogen rate, highest fresh forage yield (48360 kg ha(-1)), dry matter yield (13325 kg ha(-1)), crude protein yield (1870 kg ha(-1)) and digestible dry matter yield (8340 kg ha(-1)) was obtained at the 250 kg ha(-1) of nitrogen rate, and the highest digestible dry matter rate (62.72%) was determined at the 150 kg ha(-1) nitrogen rate. Thus, 250 kg ha(-1) nitrogen rate was the optimal dose for high forage yield and increasing nitrogen doses did not affect the ADF and NDF rates. Nevertheless, application of 300 kg ha(-1) of nitrogen decreased yield but increased crude protein yield. Therefore, a nitrogen fertilization rate of 250 kg ha(-1) is recommended for high forage yield of annual ryegrass (Lolium multiflorum L.) in the Central Black Sea Climate Zone or similar climatic conditions.
Keywords: ADF; NDF; DMY; DDMY; RFV